Shrunken pore syndrome in relation to morbidity and mortality in the population-based Malmö Diet and Cancer cohort: a generalized propensity score approach - Åkesson, Anna; Xhakollari, Liana; Laučytė-Cibulskiene, Agnė; Grubb, Anders; Larsson, Anders; Jujic, Amra; Magnusson, Martin; Christensson, Anders; Björk, Jonas (Frontiers in Epidemiology, 2025)
PurposeGlomerular filtration rate (GFR) is used for evaluating kidney function. Creatinine and cystatin C levels are the two endogenous substances used to estimate GFR (eGFRCR and eGFRCYS). The agreement between these two is reflected by the eGFRCYS/eGFRCR ratio. An eGFRCYS/eGFRCR ratio <0.70 has been strongly associated with mortality and morbidity. An explanation is a selective decrease in the filtration of substances of different masses, and this condition is referred to as “Shrunken pore syndrome” (SPS). We aim to investigate the prevalence of SPS and its association with morbidity and mortality in a well-characterized population-based cohort.MethodsThe study population consisted of 5,061 individuals from the Malmö Diet and Cancer cardiovascular cohort (MDC-CC) with baseline examinations between 1991 and 1994 and a median follow-up of 25.3 years (IQR = 5.7). The eGFRCYS/eGFRCR ratio was categorized into four groups and used to estimate a generalized propensity score for SPS to adjust for confounding factors. Individuals were matched to create a quartet (one from each eGFRCYS/eGFRCR ratio category) with similar scores. We related the eGFRCYS/eGFRCR ratio to all-cause mortality, incident cardiovascular disease, incident kidney disease, and incident diabetes using Cox proportional hazards models with shared frailty.ResultsSPS was detected in 405 individuals (8.0%). The hazard ratio (HR) for all-cause mortality was 1.6 [95% confidence interval (CI) 1.3–2.0] when comparing individuals with SPS to the reference group (eGFRCYS/eGFRCR ratio ≥ 1.0). For incident kidney disease, the association seems to stem from a low eGFRCYS rather than the eGFRCYS/eGFRCR ratio. For the other two outcomes, robust and statistically significant associations could not be found.ConclusionSPS was prevalent among middle-aged, generally healthy, individuals and led to markedly higher mortality during follow-up.